COVID-19 and community pharmacy services in Pakistan: challenges, barriers and solution for progress - Muhammad Atif; Iram Malik (Taylor & Francis Group, 2020)
In the wake of atrocious rise in COVID-19 cases, developed countries are leveraging a range of community pharmacy services with the goal of improving access to essential medication and healthcare services. While in the developing nations, including Pakistan, pharmacists are unable to perform COVID-19 containment roles in community, since presence of pharmacists at community pharmacy settings and delivery of pharmacy services have historically been plagued by shortcomings at various levels. In this document, we identified these shortcomings which need to be resolved on many fronts. Broadly, a number of intertwined government related, public related, academic curricula and pharmacist related, and drug retailers' related factors refrain community pharmacists from performing and facilitating Pakistan's fragile public and healthcare system in the midst of COVID-19 pandemic. Government led multifaceted approaches are urgently needed to strengthen this unrecognized domain and thereby effectively combat COVID-19 by utilizing community pharmacy services, as evidenced in the developed world. [Note: Part of this article is published in Pakistan Observer Newspaper; dated 17 May 2020).